On an one- and quasi-two dimensional linking hydraulic model for the complex river network-validation and application - Hanh, Nguyen Van; Can, Ngo Huy; Diep, Nguyen Van (Vietnam Journal of Mechanics, 2002)
This paper describes an approach to construct an one- and quasi-two dimensional hydraulic model for the complex river network, including various hydraulic structures. The model is based on the numerical solution of the Saint-Venant equations for river branches, the continuity equation for storages, the equation for junction conditions of the confluences, tributaries, the equation for hydraulic structures between rivers and storage cells. Cross sections are modeled as a combination of main and flood plain parts to simulate better the flow pattern. The calculating program has been developed, validated by test cases, proposed by European big hydraulic research laboratories and then applied to build a hydraulic model for the complicated Red-Thai Binh river network.